2014
DOI: 10.3389/fped.2014.00084
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea Syndrome in Children with 22q11.2 Deletion Syndrome after Operative Intervention for Velopharyngeal Insufficiency

Abstract: Introduction: Surgical treatment of velopharyngeal insufficiency (VPI) in 22q11.2 deletion syndrome is often warranted. In this patient population, VPI is characterized by poor palatal elevation and muscular hypotonia with an intact palate. We hypothesize that 22q11.2 deletion patients are at greater risk of obstructive sleep apnea (OSA) after surgical correction of VPI, due, in part, to their functional hypotonia, large velopharyngeal gap size, and the need to surgically obstruct the velopharynx.Methods: We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 24 publications
1
41
0
Order By: Relevance
“…Other than obstructive sleep apnea, clinical sleep problems have historically not been readily highlighted or systematically investigated for this population. There have been several papers reporting on the increased risk specifically of OSA in persons with 22q11DS compared to nonsyndromic children; often these studies are referencing obstructive sleep concerns in relation to surgical correction of a cleft palate or velopharyngeal insufficiency (Crockett et al, ; Heike et al, ; Kennedy et al, ; Silvestre et al, ). While awareness has been growing around the increased risk of OSA in these persons, the existence, understanding, and impact of other sleep problems in children with 22q11DS has not previously been fully addressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other than obstructive sleep apnea, clinical sleep problems have historically not been readily highlighted or systematically investigated for this population. There have been several papers reporting on the increased risk specifically of OSA in persons with 22q11DS compared to nonsyndromic children; often these studies are referencing obstructive sleep concerns in relation to surgical correction of a cleft palate or velopharyngeal insufficiency (Crockett et al, ; Heike et al, ; Kennedy et al, ; Silvestre et al, ). While awareness has been growing around the increased risk of OSA in these persons, the existence, understanding, and impact of other sleep problems in children with 22q11DS has not previously been fully addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Despite extensive research into the more common clinical presentations associated with 22q11DS, little is known about the specific sleep characteristics in this unique population. Previous studies have documented an increased risk of obstructive sleep apnea (OSA) in this population (Crockett, Goudy, Chinnadurai, & Wootten, ; Heike et al, ; Kennedy et al, ; Silvestre, Tahiri, Paliga, & Taylor, ). Beyond OSA, one prior study reported a greater prevalence of sleep problems in females with 22q11DS compared to males (Briegel, Schneider, & Schwab, ), and there is a case report of continuous spikes and waves during sleep (Valvo et al, ).…”
Section: Introductionmentioning
confidence: 88%
“…Epilepsy also associates with a higher rate of developmental delay, but not with psychiatric disorder . The relationships of epilepsy with specific psychiatric diagnoses (eg, ADHD) and other salient manifestations of 22q11.2DS, such as sleep disturbance and motor coordination problems, have not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…These defects result in the diagnostic “velo-pharyngeal insufficiency” that characterizes the syndrome [73]. Velo-pharyngeal insufficiency complicates feeding and swallowing by allowing aspiration from the mouth into the nasal sinuses [13, 16]; it is also associated with sleep apnea [74, 75], as well as speech and language difficulties including hyper-nasality at later stages due to altered airflow during articulation [76–78]. It remains uncertain, however, whether this phenotype, a likely a critical contributor to dysphagia in 22q11DS infants and children, reflects oropharyngeal structure, or altered palatal control due to hypotonia.…”
Section: Introductionmentioning
confidence: 99%